Efficiency of Islamic and Conventional Banks in Indonesia during COVID-19: A Stochastic Frontier Analysis - Dewindaru, Dini; Sari, Ermina (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
The COVID-19 pandemic has disrupted global financial systems, with the banking sector facing mounting pressures on operational efficiency and financial stability. In Indonesia, this crisis presented a critical test for both Conventional Banks (CBs) and Islamic Banks (IBs), whose structural and operational models differ significantly. This study aims to evaluate and compare the efficiency levels of CBs and IBs during the COVID-19 pandemic (2020–2022) using a quantitative approach. The Stochastic Frontier Analysis (SFA) with a Cobb-Douglas production function was employed to measure cost efficiency, while an independent samples t-test was used to determine the statistical significance of efficiency differences between bank types. A purposive sample consisting of 39 CBs and 9 IBs was analyzed based on input variables (fixed assets, deposits, and personnel costs) and output (total financing). The results reveal that CBs achieved higher efficiency scores (average = 89.39) compared to IBs (average = 82.27), with the difference being statistically significant (p < 0.001). Efficiency among CBs remained relatively stable, while IBs showed more variability and consistent decline over the period. The study identifies key contributing factors to IBs' lower efficiency, including technological constraints, lack of product standardization, and regulatory complexities. These findings underscore the need for structural reforms in the Islamic banking sector, particularly in technology adoption and regulatory harmonization. The study offers valuable insights for regulators, bank managers, and policymakers in enhancing the resilience and competitiveness of Indonesia’s dual banking system during periods of financial stress.========================================================================================================ABSTRAK - Efisiensi Bank Syariah dan Bank Konvensional di Indonesia Selama Pandemi COVID-19: Analisis Frontier Stokastik. Pandemi COVID-19 telah mengguncang sistem keuangan global, termasuk sektor perbankan yang menghadapi tekanan besar terhadap efisiensi operasional dan stabilitas keuangan. Di Indonesia, krisis ini menjadi Pelajaran berharga bagi Bank Konvensional (CBs) dan Bank Syariah (IBs) yang memiliki perbedaan struktural dan operasional yang signifikan. Penelitian ini bertujuan untuk mengevaluasi dan membandingkan tingkat efisiensi CBs dan IBs selama pandemi COVID-19 (2020–2022) melalui pendekatan kuantitatif. Metode yang digunakan adalah Stochastic Frontier Analysis (SFA) dengan fungsi produksi Cobb-Douglas untuk mengukur efisiensi biaya, serta uji t independen untuk mengetahui signifikansi perbedaan efisiensi antara kedua jenis bank. Sampel purposif terdiri dari 39 CBs dan 9 IBs, dianalisis berdasarkan variabel input (aset tetap, dana pihak ketiga, dan biaya SDM) serta output (total pembiayaan). Hasil penelitian menunjukkan bahwa CBs memiliki skor efisiensi lebih tinggi (rata-rata = 89,39) dibandingkan IBs (rata-rata = 82,27), dengan perbedaan yang signifikan secara statistik (p < 0,001). Efisiensi CBs cenderung stabil, sementara IBs menunjukkan penurunan konsisten dan variasi yang lebih besar. Faktor-faktor yang berkontribusi terhadap rendahnya efisiensi IBs mencakup keterbatasan teknologi, kurangnya standardisasi produk, dan kompleksitas regulasi. Temuan ini menekankan pentingnya reformasi struktural dalam sektor perbankan syariah, khususnya dalam adopsi teknologi dan harmonisasi regulasi. Studi ini memberikan wawasan penting bagi regulator, manajemen bank, dan pembuat kebijakan dalam meningkatkan daya tahan dan daya saing sistem perbankan ganda di Indonesia pada masa krisis keuangan.